THE HITCHIN CONNECTION IN ARBITRARY CHARACTERISTIC. (11th January 2023) - Pauly, Christian; Martens, Johan; Bolognesi, Michele; Baier, Thomas
Abstract: We give an algebro-geometric construction of the Hitchin connection, valid also in positive characteristic (with a few exceptions). A key ingredient is a substitute for the Narasimhan–Atiyah–Bott Kähler form that realizes the Chern class of the determinant-of-cohomology line bundle on the moduli space of bundles on a curve. As replacement we use an explicit realisation of the Atiyah class of this line bundle, based on the theory of the trace complex due to Beilinson–Schechtman and Bloch–Esnault.